Manufacturing organization and management / Harold T. Amrine ... [et al.] - Amrine, Harold T.; Amrine, Harold T. (Prentice Hall international series in industrial and systems engineering, 1993)
Featuring short case study applications, this new edition explores the principles, practices, functions, and challenges of manufacturing management. It incorporates the latest developments in technology, methodology, and practice, while retaining fundamentals of material purchasing, inventory control, and production schedules. For production and manufacturing management professionals.